Simultaneous production of biomethane and food grade CO2 from biogas: an industrial case study. Issue 1 (23rd November 2018) - Esposito, Elisa; Dellamuzia, Loredana; Moretti, Ugo; Fuoco, Alessio; Giorno, Lidietta; Jansen, Johannes C.
Abstract : This work presents a case study on the first large-scale industrial biogas upgrading process with simultaneous purification of methane and CO2 in one of Europe's largest biogas production and purification plants in Northern Italy. Abstract : This work presents a case study on the first large-scale industrial biogas upgrading process with simultaneous purification of methane and CO2 in one of Europe's largest biogas production and purification plants in Northern Italy. A preliminary study was performed on a pilot plant, constructed as a model of the industrial plant where the final experiments were performed. The full-scale anaerobic digestion plant has a digestive capacity of 400 000 tonnes of biomass per year and it can treat 6250 m 3 h −1 of biogas. The first objective was a biogas upgrading process that achieves distribution grid-quality methane via different purification steps. The second objective and most innovative aspect is the further purification of CO2 from a useless waste product to a high purity gas for the food and beverage industry. The chemical purity of different process streams was analysed by a certified laboratory and was compared with the guidelines of the European Industrial Gas Association and International Society of Beverage Technologists (EIGA/ISBT) for CO2 used in the food industry. The microbiological purity was found to be far below the limit values defined in the European Collaborative Action. With a purity of 96.3 vol%, methane respects the purity requirement for the household network. With a purity of 98.1 vol% before, and 99.9 vol% after the final distillation process, CO2 proves to be chemically and microbiologically suitable for food applications, thus closing the CO2 loop in biogas production. An evaluation of the economic and energetic aspects and a comparison with alternative purification processes highlights the profitability of the process.